LITERATURE REVIEW: IMPLEMENTATION OF A BIOLOGY PRACTICAL GUIDE IN THE FORM OF A FLIPBOOK INTEGRATED WITH GUIDED INQUIRY FOR MERDEKA CURRICULUM IN HIGH SCHOOL STUDENTS - Roshita Putri, Nazzla; Relsas Yogica; Syamsurizal; Ria Anggriyani (BIOCHEPHY: Journal of Science Education, 2024)
A practical activity requires a guide that includes practical objectives, practical processes, tools and materials, and observation sheets for the practical activity. These guides are sometimes referred to as practical guidebooks. In particular, practicum instructors will need to be tech-savvy in the next wave of educational technology. The study's goal is to ascertain how biology flipbooks integrating guided inquiry and practical guidebooks are implemented for high school pupils. A literature review is one of the qualitative research strategies used in this kind of study. methods for choosing literature based on guided inquiry, Flipbooks, Practical Guidebooks, and Keywords. The literature is derived from research findings found on Google Scholar, with a 10-year publication window. A synthetic matrix based on reference sources, sample types, procedures, interventions, and findings is used in the literature study process. The implementation of the practical guidebook in the form of a flipbook for high school students pursuing an autonomous curriculum is found to be highly significant as a learning medium in practical activities due to its ability to support and facilitate the learning process.